Gaya Bahasa Persuasif dalam TikTok Delta Hesti - Rahma Fadilah, Alifa; Eva Ardiana Indrariani; Latif Anshori Kurniawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study analyzes how persuasive language style is used by Delta Hesti in sales activities through TikTok, especially in live streaming and product reviews, with the theoretical aim of adding to sociolinguistic studies in the context of digital business communication by exploring the role of persuasive language style in increasing consumer satisfaction with sales activities on social media, both directly through live streaming or indirectly through product reviews. Meanwhile, the practical aim is to provide insight for business actors who use the TikTok platform as a sales tool regarding the importance of selecting and using persuasive language to increase consumer satisfaction and loyalty. Using a descriptive qualitative method with non-participatory observation, data was collected from live streaming videos of Delta Hesti TikTok sales account. The results of the analysis show that there are two types of persuasive language styles used, namely language style based on sentence structure, namely repetition, and language style based on the indirectness of meaning, namely hyperbole and metonymy. The most dominant language style found is repetition.